2011
DOI: 10.1016/j.lindif.2010.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Self-regulation mediates the relationship between learner typology and achievement in at-risk children

Abstract: A person-centered approach was used to explore the mediating role of self-regulation between learner typology at age 8 and academic achievement at age 14while controlling for domainspecific achievement in a longitudinal sample of 113 children born to adolescent mothers. Children were classified into one of 5 learner typologies at age 8based on interactive patterns of intellectual, achievement, and adaptive abilities. Typology classification explained significant variance in both reading and mathematics achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…As regards children with learning disabilities, previous research had confi rmed that self-regulation mediated the relationship between type of learning disability and reading and mathematical achievement for children (Weed et al 2011). In another study, subjects with dyslexia were found to respond faster than both the other groups in response time (p < 0.05), clearly showing a signifi cantly higher cognitive impulsivity than the other groups.…”
Section: Introductionmentioning
confidence: 89%
“…As regards children with learning disabilities, previous research had confi rmed that self-regulation mediated the relationship between type of learning disability and reading and mathematical achievement for children (Weed et al 2011). In another study, subjects with dyslexia were found to respond faster than both the other groups in response time (p < 0.05), clearly showing a signifi cantly higher cognitive impulsivity than the other groups.…”
Section: Introductionmentioning
confidence: 89%
“…in 1982,[108] the self-regulation model states that the human mind will identify goals to modify mentation, volition and tasks performance in face of a challenge or adversity to attain more desirable outcomes. [109] These outcomes include better mental health against the threat of mortality,[110] adherence to law, standards and norms, proactive coping skills[111] especially in poverty,[112113] maintaining adult attachment relationships and their salvage,[114] academic goals attainment,[115116] abstinence from substance addiction[117] and also protective effects against disordered eating. [118] Moreover, some researchers consider self-regulation as an adaptive capacity which can be trained up with repeated exercises[119120] of both the mind and the body, with the added concept that it is a limited resource dependent upon blood sugar[121] and physical stamina.…”
Section: Can Pain Models Explain Pain Catastrophizing?mentioning
confidence: 99%
“…Dysfunction of the dopamine (neurochemical) system is responsible for some symptoms including impulsivity (Winstanley et al, 2006). Moreover, Weed et al (2011) and Barahmand et al (2015) confirmed that children with SLD, as well as children with impulsivity, have impaired frontal/ prefrontal function, which Crews and Boettiger (2009) confirmed as overseeing behavioral control through executive functions, which include abstract thinking, motivation, planning, attention to tasks, and the inhibition of impulsive responses. Thus, it can be suggested that the achievement of children with SLD is at stake because of their executive function deficits, as well as because of their impulsive temperament.…”
Section: Causes Associated With Impulsivitymentioning
confidence: 90%
“…Previous results (Purvis & Tannock, 2000) have reported a prevalence of impulsivity, especially among students with dyslexia, and have shown that children with ADHD and a reading disorder performed worse than children with ADHD without reading disorder in an inhibitory control task, which suggests an additional impulsivity effect of dyslexia. Weed et al (2011) found that children with dyslexia tend to be faster in their responses and show higher cognitive impulsivity than other groups of children. However, Nagle and Thwaite (1979) found that children with SLD are not more impulsive compared with children without disabilities, rather they use poor strategic behaviors when processing information.…”
Section: Cognitive and Behavioral Aspects Of Impulsivitymentioning
confidence: 97%
See 1 more Smart Citation